The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/jcm12144713
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Criteria and Prognostic Relevance of Sarcopenia in Patients with Inflammatory Bowel Disease—A Systematic Review

Abstract: Background: Sarcopenia is a syndrome characteristic in elderly patients and is also associated with a significant proportion of chronic disorders such as inflammatory bowel disease (IBD). In this case, it can lead to a worse prognosis of the disease and a decreased quality of life. Study Aim: This study aims to identify the best ways to diagnose sarcopenia in patients with IBD, establish its impact on the course of the disease, and find preventive methods to counteract the effects of sarcopenia in the outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…A recent systematic review of 18 studies found that the prevalence of sarcopenia among CD patients, ranges from 16 to 100%, and is higher than 50% in more than half of the included studies. This large variability might be explained by the lack of a universal definition of sarcopenia, by the anthropometric and socio-cultural heterogeneity of the population of interest, alongside with the high variability of muscle mass indices and thresholds used to identify sarcopenic patients [ 44 ]. The European Working Group on Sarcopenia in Older People (EWGSOP) identifies low muscle strength, and low muscle quantity and quality as mandatory features to diagnose sarcopenia; physical performance status is used to quantify the severity of sarcopenia [ 45 ].…”
Section: Nutritional Optimizationmentioning
confidence: 99%
“…A recent systematic review of 18 studies found that the prevalence of sarcopenia among CD patients, ranges from 16 to 100%, and is higher than 50% in more than half of the included studies. This large variability might be explained by the lack of a universal definition of sarcopenia, by the anthropometric and socio-cultural heterogeneity of the population of interest, alongside with the high variability of muscle mass indices and thresholds used to identify sarcopenic patients [ 44 ]. The European Working Group on Sarcopenia in Older People (EWGSOP) identifies low muscle strength, and low muscle quantity and quality as mandatory features to diagnose sarcopenia; physical performance status is used to quantify the severity of sarcopenia [ 45 ].…”
Section: Nutritional Optimizationmentioning
confidence: 99%
“…In the realm of rehabilitation, interventions vary widely, encompassing several key aspects. Firstly, there are goal-oriented treatments tailored to alter the trajectory of a condition [ 14 ]. Secondly, a focus on reducing activity limitations is crucial, involving specific measures such as spasticity reduction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%